Learning from Experience in NSW?1. Issue 2 (28th April 2016) - Bell, Brian; Dollery, Brian; Drew, Joseph
Abstract : While the bulk of the empirical evidence shows that municipal mergers do not improve the performance of local authorities, Australian policy‐makers nonetheless continue to impose council amalgamation, as illustrated by the current New South Wales Fit for the Future local government reform process. This paper first critically examines the empirical evidence employed by the Independent Local Government Review Panel on the impact of the 2004 council mergers. We argue that this evidence is flawed. We then provide an empirical assessment of the municipal mergers, which occurred over 2000–2004 with our sample drawn from Group 4 councils in the New South Wales variant of the Australian Local Government Classification System. Group 4 councils represent a group of significant regional cities and town councils with similar operational activities. We demonstrate that merged councils have not performed any better than their unmerged peers over the period 2004 to 2014. The paper concludes with some brief policy implications for local government reform in New South Wales and elsewhere.